Assessing clinical correlates of self-rated disability in patients with multiple sclerosis. (26th June 2015) - Magistrale, Giuseppe; Medori, Rossella; Cadavid, Diego; Argento, Ornella; Incerti, Chiara; Pisani, Valerio; Caltagirone, Carlo; Bozzali, Marco; DeLuca, John; Nocentini, Ugo
Background: Multiple sclerosis (MS) is associated with significant impairment. Objective: The objective of this article is to identify and compare clinical measures that can predict self-rated disability in patients with MS using the World Health Organization Disability Assessment Schedule II (WHODAS-II). Methods: Patients with MS and healthy controls were consecutively recruited at one center. Patients were evaluated for cognitive function assessment, neurological status, perceived disability, mood, fatigue and disease duration. Controls underwent neuropsychological evaluation only. Data were analyzed using multivariate regression. Results: WHODAS-II total score was predicted by fatigue ( p  < 0.001) and neurological status ( p  < 0.05). Student's t test comparisons between published WHODAS-II normative data and the enrolled cohort of patients with MS showed significantly worse ( p  < 0.05) scores for patients on mobility, self-care, life activities, participation and total score domains, but not in cognition. Group differences between patients with MS ( n  = 61) and controls ( n  = 61) were significant in all cognitive measures except one verbal memory test subscale. Memory function correlated best with the social participation domain of the WHODAS-II. Conclusions: Self-reported disability in patients with MS was most strongly influenced by fatigue and to a lesser extent by physical disability. Although cognitive function does affect self-assessment of disability, this is not captured by patients on the WHODAS-II cognitive domain.